Sagot :
Answer:
1. (2, 4)
2. (-1/5, 2/5)
3. (1,6)
Step-by-step explanation:
1.
(y = 2x
(x + y = 6
x + 2x = 6
3x = 6
x = 2
y = 2x
y = 2(2)
y = 4
2.
5x + 10y = 3
x = -½y
5(-1/2y) + 10y = 3
-5/2y + 10y = 3
7.5y=3
y=2/5
5x +10y = 3
5x + 10(2/5) = 3
5x + 4 = 3
5x = 3-4
5x = -1
x = -1/5
3.
y - x = 3x + 2 ------- y - 4x = 2 ------- y= 2 +4x
2x + 2y = 14
2x + 2(2 + 4x) = 14
2x + 4 + 8x = 14
10x = 14 - 4
10x = 10
x = 1
y = 2 + 4x
y = 2 + 4(1)
y = 6
Step-by-step explanation:
Answer:
1.equation
2.equation
3.inequality
4.equation
5.equation